2008
DOI: 10.1159/000144491
|View full text |Cite
|
Sign up to set email alerts
|

Chyle Fistula after Neck Dissection for an Unusual Breast Cancer Recurrence

Abstract: Background: Chyle fistula is one of the rare complications of neck dissections. Even though no consented algorithm for the management of this entity has been established yet, conservative treatment options including somatostatin analogues have been suggested as an adequate modality for low output fistulas. Case Report: Here we present a patient with a right-sided neck fistula which was resistant to conventional treatment, and was finally treated by surgery. The neck dissection was performed for a malignant rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, not every CL will respond completely to octreotide therapy alone. In our literature review, two patients required surgical reexploration for control of their CL, despite a trial of octreotide [ 23 , 25 ]. Most authors agreed that if there is no reduction in drain output after 5 days of octreotide therapy then surgical exploration is indicated [ 39 ].…”
Section: Treatment Options For Chyle Leaksmentioning
confidence: 99%
“…However, not every CL will respond completely to octreotide therapy alone. In our literature review, two patients required surgical reexploration for control of their CL, despite a trial of octreotide [ 23 , 25 ]. Most authors agreed that if there is no reduction in drain output after 5 days of octreotide therapy then surgical exploration is indicated [ 39 ].…”
Section: Treatment Options For Chyle Leaksmentioning
confidence: 99%
“…Fifty-one reports were retrieved and assessed for eligibility. Finally, 40 articles were shortlisted and included in this review 7 - 46 . ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the 40 studies, 139 patients were reported to have CL after head and neck surgeries (26 left neck dissections, 4 right neck dissections, 19 bilateral neck dissections, 85 neck dissections with side unspecified, and 6 patients who underwent other procedures of the neck such as lobectomy, thyroidectomy, or parathyroidectomy) 7 - 46 . ( Table 1 , Supplementary Table 1 )…”
Section: Resultsmentioning
confidence: 99%
“…To date, the reported incidence of chylous fistula after breast surgery is approximately 0.5%, and only a few cases after axillary lymph node dissection or mastectomy have been reported. [ 3 , 4 ] In most cases, the fistula developed after axillary lymph node dissection, and <10% patients received sentinel lymph node biopsy (SLNB). It is very difficult to predict injury to the lymphatic trunks preoperatively or to identify this during surgery because of its rare occurrence during axillary or chest wall surgery; there are also no well-known risk factors.…”
Section: Introductionmentioning
confidence: 99%